HUBUNGAN SELF-EFFICACY DENGAN MAKNA HIDUP PADA MAHASISWA AKHIR - Dhenia Ayu Khatira (Universitas HKBP Nommensen, 2021)
This study aims to find out relationship between self-efficacy and the meaning of life. The Final students who are in the late adolescent category have two demands, first demands it is in the non-academic scope, the search for the meaning of life and the academic scope, the completion of the final project. This study aims to determine the relationship between self-efficacy and the meaning of life in final year students who are working on their thesis. Participants in this study were 102 students who were completing their thesis. The results of the data analysis conducted show that there is a relationship between self-efficacy and the meaning of life. This result implies that self-efficacy has an important role for the meaning of life, where the existence of self-efficacy makes it easier for individuals to find the meaning of their life.